The routine use of synovial alpha-defensin is not necessary. (May 2020) - Amanatullah, Derek F.; Cheng, Robin Z.; Huddleston III, James I.; Maloney, William J.; Finlay, Andrea K.; Kappagoda, Shanthi; Suh, Gina A.; Goodman, Stuart B.
Abstract : Aims: To establish the utility of adding the laboratory-based synovial alpha-defensin immunoassay to the traditional diagnostic work-up of a prosthetic joint infection (PJI). Methods: A group of four physicians evaluated 158 consecutive patients who were worked up for PJI, of which 94 underwent revision arthroplasty. Each physician reviewed the diagnostic data and decided on the presence of PJI according to the 2014 Musculoskeletal Infection Society (MSIS) criteria (yes, no, or undetermined). Their initial randomized review of the available data before or after surgery was blinded to each alpha-defensin result and a subsequent randomized review was conducted with each result. Multilevel logistic regression analysis assessed the effect of having the alpha-defensin result on the ability to diagnose PJI. Alpha-defensin was correlated to the number of synovial white blood cells (WBCs) and percentage of polymorphonuclear cells (%PMN). Results: Intraobserver reliability and interobserver agreement did not change when the alpha-defensin result was available. Positive alpha-defensin results had greater synovial WBCs (mean 31, 854 cells/μL, SD 32, 594) and %PMN (mean 93.0%, SD 5.5%) than negative alpha-defensin results (mean 974 cells/μL, SD 3, 988; p < 0.001 and mean 39.4% SD 28.6%; p < 0.001). Adding the alpha-defensin result did not alter the diagnosis of a PJI using preoperative (odds ratio (OR) 0.52, 95% confidence interval (CI) 0.14 to 1.88; p = 0.315) or operative (OR 0.52, CI 0.18 to 1.55; p = 0.242) data when clinicians already decided that PJI was present or absent with traditionally available testing. However, when undetermined with traditional preoperative testing, alpha-defensin helped diagnose (OR 0.44, CI 0.30 to 0.64; p < 0.001) or rule out (OR 0.41, CI 0.17 to 0.98; p = 0.044) PJI. Of the 27 undecided cases with traditional testing, 24 (89%) benefited from the addition of alpha-defensin testing. Conclusion: The laboratory-based synovial alpha-defensin immunoassay did not help diagnose or rule out a PJI when added to routine serologies and synovial fluid analyses except in cases where the diagnosis of PJI was unclear. We recommend against the routine use of alpha-defensin and suggest using it only when traditional testing is indeterminate. Cite this article: Bone Joint J 2020;102-B(5):593–599.